Analisis Kesadaran Masyarakat Dalam Melakukan Pembayaran Zakat Pertanian (Studi Kasus Petani Padi di Desa Pasar Sayur Matinggi Kec. Dolok Sigompulon Kab. Padang Lawas Utara) - Rambe, M. Jepri Pratama; Arif, Muhammad; Nasution, Juliana (Universitas Labuhanbatu, 2022)
This study was conducted because there is a low awareness of the community in the village of Pasar Sayur Matinggi in issuing agricultural zakat. It can be marked by the increasing number of farmers in Pasar Sayur Matinggi village but the stable welfare of the community even tends to decrease. Research methods in this study there is a descriptive qualitative method using field research methods. In the study using interview techniques, observation and documentation with a sample of 17 people. Data analysis techniques in this study using domain analysis, taxonomic analysis, and composional analysis. Then get the results that the people in the village vegetable market Matinggi enough to understand about zakat fitrah alone, because zakat fitrah become hereditary habits that are often done in the community when the end of Ramadan, so that the knowledge of the people in the village vegetable market Matinggi is good enough if the zakat fitrah. Some people distribute their zakat in the wrong way and they don't care about the provisions, it's just that they feel that they have spent some of their property, they have been calculated to pay zakat. From the explanation of the previous chapter, the results obtained by the community will be less awareness of paying zakat based on several factors including, low public education in Pasar Sayur Matinggi village so that it does not care about the obligation of Zakat, then social factors that prioritize the closest people even though if zakat is distributed to Amil Zakat, the distribution will also be evenly distributed. And the last customs or habits of the people who make people still reluctant to explore the zakat and also the role of zakat. Whereas the potential of zakat contained in the community in the village of Pasar Sayur Matinggi in general is very good. It can be proven based on the extent of agricultural land in the village of Matinggi vegetable market is quite extensive so that agricultural products have reached nishabnya. If implemented and distributed properly by farmers so that it will have an impact on the welfare of the people in the village of Pasar Sayur Matinggi.